ANALISIS PENGENDALIAN PERSEDIAAN BARANG MENGGUNAKAN METODE PERIOD ORDER QUANTITY - Herlambang, Andri; Amri, Syahputra; Andrean, Reza (Jurnal Manajemen Rekayasa dan Inovasi Bisnis, 2024)
This research aims to analyze and create an order scheduling system using the Period Order Quantity (POQ) method so that companies can schedule orders optimally and reduce ordering costs at the Medan Battery Shop. Companies can control inventory and increase their ability to plan the procurement of goods according to consumer needs. The data used in the research is the sales period in May - October 2023. The calculation results show that the company can order goods optimally to avoid stock shortages when selling, namely that orders are made once every 9 days with an order frequency of 140 pcs per order and the company must have a safety stock of 13 pcs to anticipate an increase in the number of purchases or You can place an order when there are 151 pieces left in stock.